Experimental study techniques for the early speech perception (2014)
The early speech perception began to be studied at the beginning of the 1970s, but only developed fully ten years later due to the appearance and adaptation of new empirical methods and technological tools. The article reviews the experimental methods that can be used to study early speech perception in children under the age of one, and discusses some of the most relevant theoretical conclusions reached thanks to their application. The objective is to provide an overview of the methodological and theoretical situation of the study of speech perception during the first year of life.